Headscarves and the CJEU: Protecting fundamental rights and pandering to prejudice, the CJEU does both. Issue 2 (April 2022) - Howard, Erica
The CJEU judgment in the two latest Islamic headscarf cases was handed down in July 2021. The judgment allows employers to ban the wearing of religious and other symbols by employees, but it does specify under what conditions this can be done. This article builds on a previous article on the opinion of AG Rantos and the Shadow Opinion of former AG Sharpston and analyses the judgment in detail. It argues that the judgment is an improvement on the previous CJEU headscarf judgments in that it provides more protection for fundamental human rights. However, the CJEU also appears to allow employers to a certain extent to pander to the prejudicial wishes of their customers. The article concludes that the judgment presents a small glimmer of hope that the CJEU might be moving – albeit very slowly - towards more protection of Muslim women who want to wear headscarves at work for religious reasons.